SPECTRAL DENSITY OF STATES IN QUANTUM NANOCLUSTERS - Zharekeshev, Isa Kh. (Recent Contributions to Physics, 2018)
The density of states is studied by using disordered Hamiltonians for quantum systems. The electron spectrum of nanoclusters is calculated for various type of disorder.